2021
DOI: 10.21037/atm-21-631
|View full text |Cite
|
Sign up to set email alerts
|

Identification of diagnostic and prognostic signatures derived from preoperative blood parameters for oral squamous cell carcinoma

Abstract: Background: We aimed to develop novel diagnostic and prognostic signatures based on preoperative inflammatory, immunological, and nutritional parameters in blood (PIINPBs) by machine learning algorithms for patients with oral squamous cell carcinoma (OSCC). Methods: A total of 486 OSCC patients and 200 age and gender-matched non-OSCC patients who were diagnosed and treated at our institution for noninfectious, nontumor diseases were retrospectively enrolled and divided into training and validation cohorts. Bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Santos et al (2021) demonstrated that the combination of PLR, NLR, dNLR, and PLR + NLR served as robust prognostic biomarkers for locally advanced cervical cancer [46]. A series of recent studies [47][48][49][50] have focused on in ammatory markers derived from complete blood count parameters, which have predictive effects on the survival and prognosis of malignant tumors. A recent study indicated the signi cant roles of NF-κB, miR-221/222, and Sdc1 in the pathogenesis of recurrent endometriosis [51]; however, the exact mechanism remains elusive.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Santos et al (2021) demonstrated that the combination of PLR, NLR, dNLR, and PLR + NLR served as robust prognostic biomarkers for locally advanced cervical cancer [46]. A series of recent studies [47][48][49][50] have focused on in ammatory markers derived from complete blood count parameters, which have predictive effects on the survival and prognosis of malignant tumors. A recent study indicated the signi cant roles of NF-κB, miR-221/222, and Sdc1 in the pathogenesis of recurrent endometriosis [51]; however, the exact mechanism remains elusive.…”
Section: Discussionmentioning
confidence: 99%
“…In the past decade, research has primarily focused on in ammatory markers derived from complete blood count (CBC) parameters, such as neutrophils (N), monocytes (M), lymphocytes (L), platelets (P), albumin (ALB), hemoglobin (Hb), platelet-to-lymphocyte ratio (PLR), neutrophil-to-lymphocyte ratio (NLR), lymphocyte-to-monocyte ratio (LMR), and systemic immune-in ammation index (SII). These markers have demonstrated predictive effects on the survival and prognosis of malignant tumors, including colorectal cancer [22], gastric cancer [23], breast cancer [24][25][26], lung cancer [27][28], rectal cancer [29], ovarian cancer [30], bladder cancer [31], neurological diseases [32], and oral cancer [33]. Multiple lines of evidence suggest that radiation enteritis is an in ammatory reaction [34][35][36][37][38].…”
Section: Introductionmentioning
confidence: 99%